Chromium complexes supported by the bidentate PN ligands: synthesis, characterization and application for ethylene polymerization. Issue 38 (5th September 2018) - Zheng, Quande; Zheng, Dejuan; Han, Binghao; Liu, Shaofeng; Li, Zhibo
Abstract : Chromium complexes bearing phosphine–imine ligands are highly active for ethylene polymerization and produce HDPE with a high molecular weight. Abstract : Chromium-based complexes are among the most important catalysts in the field of ethylene polymerization and oligomerization. Heterogeneous Cr Phillips catalysts account for more than one-third of the commercialized high density polyethylene (HDPE). In this contribution, chromium complexes, L CrCl3 (Cr1–Cr4 :L = 2, 6-R 1 -4-R 2 -C6 H2 -NCH-C6 H4 -2-PPh2 ;Cr1 : R 1 = H, R 2 = H;Cr2 : R 1 = Me, R 2 = H;Cr3 : R 1 = i Pr, R 2 = H;Cr4 : R 1 = Ph2 CH, R 2 = i Pr), have been synthesized and characterized by elemental analysis, ESI and IR spectroscopy. The molecular structures ofCr3 andCr4 are defined by X-ray diffraction, revealing a distorted octahedral geometry around the chromium center in both structures. In the presence of an aluminum cocatalyst, complexesCr1–Cr4 show moderate to high activities toward ethylene polymerization. The nature of the catalysts and various reaction conditions, such as the nature and the amount of cocatalyst, reaction time and temperature, are investigated in detail. The results show that the title complexes have good thermal stability and the substituents on the ligands significantly affect the catalytic properties. Particularly, complexCr4 can produce HDPE with a high molecular weight up to 68.3 × 10 4 g mol −1 due to the suppression of the chain transfer/termination by the introduction of bulky Ph2 CH groups.